Sistema de gestión de seguridad y salud ocupacional para la empresa marin rios constructores s.a.c. basado en la norma ohsas 18001:2007 - Gaitán Cueva, Francisco Esteyner (2017)
The present research work is based on the development of a Occupational Health and Safety Management System in the mining civil works for the Marín Ríos Constructores SAC Company, taking as reference: Law N° 29783. "Law of Safety and Health at Work ", the D.S. 024 - 2016 - EM. Occupational Safety and Health Regulations in Mining, and the technical standard G.050 "Safety during Construction". In turn, all of the aforementioned regulations regarding occupational safety and health refer to the requirements and structure of the OHSAS 18001:2007 standard, which is an international standard for occupational health and safety management systems. Therefore, in the first instance, the work team was set up, the scope was defined, and then the company's current situation was diagnosed against the requirements proposed by OHSAS 18001: 2007, for which interviews, surveys, Documentary analysis, and direct observation about the procedures, rules and legal bases that are carried out to manage the security in the Company and to identify the risks present in the workstations and in the activities carried out by the personnel. Subsequently, a statistical analysis of the incidents occurred in the Company was carried out to obtain the accident rate and thus to know the future trend if corrective measures are not taken, the FODA matrix was also elaborated to plan the strategies, minimizing the weaknesses And threats, and maximizing strengths and opportunities. Finally, corrective action plans were established for the development of the occupational health and safety management system for the Company Marin Ríos Constructores S.A.C. Based on the OHSAS 18001: 2007 standard and an implementation plan was drawn up to reduce safety levels and mitigate occupational hazards and affect workers' health.